Pengaruh Belanja Kesehatan Pemerintah Terhadap Angka Kematian Bayi Di Indonesia Dengan Kualitas Tata Kelola Pemerintahan Sebagai Variabel Moderasi - Indah Wulandari; Fandy Triawan (Universitas Negeri Padang, 2026)
This study examines the effect of government health spending on infant mortality in Indonesia and tests the moderating role of governance quality, proxied by government effectiveness and voice and accountability. Using a quantitative time-series approach with data from 2004–2024 obtained from the World Development Indicators (WDI), Worldwide Governance Indicators (WGI), and the Indonesian Ministry of Finance, this research employs multiple linear regression and Moderated Regression Analysis (MRA) using Stata 14. The results indicate that in the baseline model, health spending significantly reduces infant mortality. However, after including interaction terms, the direct effect of health spending becomes insignificant, while the interaction between health spending and both governance indicators is statistically significant. This confirms that the effectiveness of health spending in reducing infant mortality is conditional on the quality of governance. The findings imply that increasing the health budget must be accompanied by bureaucratic strengthening, policy implementation effectiveness, enhanced accountability, and greater public participation. This study contributes to the public finance and health system governance literature by providing empirical evidence from Indonesia